Manufacturing Engineering Training for Vocational High Schools Students in East Priangan, West Java, Indonesia - Aceng Sambas; Gugun Gundara; Sri Ayu Fujilestari; Mujiarto Mujiarto (International Journal of Research in Community Services, 2023)
The main problem in the manufacturing process in vocational schools is the limited number of manufacturing machines for the practical process because the equipment is very expensive. Therefore, the main objective of this activity is to provide training on manufacturing processes both theoretically and experimentally to vocational high school students in Tasikmalaya City. The results of this activity indicate that vocational high school students gain experience and knowledge in operating manufacturing machinery from start to finish.